Repurposing Siderophores as Antitubercular Agents - Karuna Gokarn; Ramprasad Balikaran Pal (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Background: The problem of drug-resistant Mycobacterium tuberculosis (M.tb) is alarming and therefore there is an immediate need for alternative or complementary drugs. This could be achieved by repurposing existing FDA-approved drugs. In this study, the anti-tuberculosis activity of microbial siderophores was evaluated against drug-resistant M.tb isolates. The cell cytotoxicity of the siderophores was also evaluated on mammalian cell lines. Methods: Drug susceptibility testing to assess the anti-tubercular effect of the siderophores was done using the Mycobacteria Growth Indicator Tube method. Mammalian cell cytotoxic effects of the siderophores was evaluated by the MTT assay. Results: The siderophores assessed were found to be effective individually and in the presence of primary or secondary anti-TB drugs routinely prescribed, but that are not effective on drug-resistant M.tb isolates. Interestingly, the MIC of a siderophore decreased when assessed along with anti-tubercle drugs. No significant cell cytotoxicity was observed. Conclusion: Siderophores are safe and may be useful additions to the anti-TB drug regimen aiding in conquering drug-resistant tuberculosis.